The Relationship Between the Intensity of Deep Dialogue Use and Students’ Motivation in Fiqh Learning at MTs Al–Marzuqin Pekanbaru - Syahraini Tambak; Firdaus Firdaus; Musaddad Harahap; Desi Sukenti (CV. Zamron Pressindo, 2025)
Research Objective – This study aims to examine the relationship between the intensity of deep-dialogue-based instruction and students’ motivation in learning fiqh at MTs Al-Marzuqin Pekanbaru. It seeks to address the motivational challenges commonly found in traditional Islamic jurisprudence education. Methodology – Employing a quantitative correlational design, the study involved 60 eighth-grade students who had experienced dialogical fiqh instruction for one semester. Data were collected using validated Likert-scale questionnaires measuring deep dialogue intensity and student motivation, grounded in Self-Determination Theory. Descriptive statistics, Kolmogorov–Smirnov normality tests, and Pearson correlation analysis were used for data analysis. Findings – The findings revealed a high level of dialogical engagement (M = 78.45) and student motivation (M = 81.12). The Pearson correlation test showed a strong and statistically significant positive relationship between the two variables (r = 0.698, p < 0.001). This suggests that the more frequently and meaningfully deep dialogue is used in fiqh instruction, the higher the students’ motivation tends to be. Research Implications/Limitations – The study highlights the pedagogical value of integrating deep-dialogue methods in Islamic education to foster motivation. However, it is limited to a single institution and does not account for long-term learning outcomes. Originality/Value – This research contributes to the growing body of literature advocating for dialogical pedagogy in religious education by empirically demonstrating its motivational benefits. It also bridges classical Islamic teaching traditions (al-ḥiwār) with contemporary psychological theories, offering a culturally grounded and evidence-based instructional model